A influência do polimorfismo da enzima conversora de angiotensina (rs1799752) e nível de atividade física sobre parâmetros hemodinâmicos e autonômicos em adolescentes - SENA, Carlan da Silva (2021)
Objective: To analyze the influence of the ACE gene polymorphism (rs1799752) and level of physical activity on hemodynamic and autonomic variables and on the odds ratio of a cardiovascular event in adolescents. Materials and methods: This work consists of an analytical and transversal study, composed of 136 adolescents between 14.89 ± 1.64 years of age, students from a public school in São Luís, Maranhão. Participants were divided into Active Group (GA) and Sedentary Group (GS) taking into account the genotype DD, DI and II. The level of physical activity, sexual maturation, anthropometric measurements, oral cells were collected for subsequent genotyping of the angiotensin-converting enzyme, blood pressure measurement and analysis of heart rate variability. In the statistical analysis, the Kolmogorov-Smirnov normality test was used, to analyze the differences between the groups, the unpaired t test and the Two-way ANOVA with the Bonferroni posthoc test were used to assess the association between qualitative variables. the chisquare test was performed, the Hardy-Weinberg balance was tested by the Fisher test. The odds ratio (Odds Ratio) was calculated for hemodynamic and autonomic variables to estimate the relative risk. Results: The main finding of this study was that the GS with the DD genotype showed greater sympathetic modulation (BF%: 48.34 ± 11.71 vs 39.7 ± 12.21) and decreased vagal action (AF%: 51, 66 ± 11.71 vs 60.3 ± 12.21, and BF / AF: 1.16 ± 0.79 vs 0.80 ± 0.49) in relation to GA with the DD genotype. Higher systolic blood pressure was also observed in the GS group with the DD genotype (SBP: 114, 3 ± 11.7 vs 107.9 ± 12 mmHg). When only GA vs GS were related, it was observed that GA had lower values of systolic blood pressure (SBP: 110.8 ± 1.35 vs 114.5 ± 1.63 mmHg) and diastolic blood pressure (DBP: 64.34 ± 0.85 vs 67.46 ± 1.06 mmHg) respectively, in addition to greater vagal modulation (AF%: 59.25 ± 15.76 vs 53.4 ± 15.68 and BF / AF: 84 ± 0.77 vs 1.04 ± 0.74) and less sympathetic modulation (BF%: 40.75 ± 15.76 vs 45, 68 ± 15.44). Still, when evaluating the odds ratio of a cardiovascular event to occur in a group, we found that the GS DD has a greater chance of occurrences in relation to the GA DD group, as verified for the variables BF%, AF%, BF / AF (Odds ration: 2.6286) and PAS (Odds ration: 5.5862). Conclusion: Adolescent with DD genotype of ACE polymorphism, and sedentary, has less cardiac autonomic modulation, greater SBP, greater chance of developing cardiovascular diseases, thus, being physically active helps to improve these parameters, decreasing cardiovascular risk.